Spatial dynamics of tuned and mistuned bladed disks with cylindrical and wedge-shaped friction dampers - Panning, Lars; Sextro, Walter; Popp, Karl (International Journal of Rotating Machinery)

Vibration Damping by Friction Forces -Theory and Applications - Popp, Karl; Panning, Lars; Sextro, Walter (Journal of Vibration and Control)

Optimierung des Schwingungsverhaltens elastischer Strukturen mit Reibfugen am Beispiel von Turbomaschinenschaufeln - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW))

On forced vibration of shrouded turbine blades - Szwedowicz, J; Sextro, Walter; Visser, R; Masserey, P.A (ASME Turbo Expo 2003, collocated with the 2003 International Joint Power Generation Conference)
Numerical predictions of the forced vibration of a disc assembly including frictional effects between the shrouds are presented concerning engineering needs for the blade design process. Assuming a tuned disc assembly, numerical static, free and then forced vibration analyses of a shrouded turbine blade measured in the spin pit are performed systematically. For the excitation forces of an air jet evaluated from the fairly linear behavior of the experimental blade resonance peaks, the reliability of the proposed approach is validated through the very close agreement of the computed and measured resonant peaks. These resonant peaks demonstrate either a fairly linear behavior or a non-linear one like the jump effect of blade resonance amplitudes, or elastic impacts between the shrouds. Also, the damping performance for different contact configurations between the shrouds is numerically analyzed. These numerical results indicate that the shrouds generate higher frictional damping for small angles (0--30 deg) between the circumferential direction and the normal vector to the contact surface. Copyright {©} 2003 by ASME
Keywords: Turbine blades; Vibration

Piezoelectric transformers - state of the art and development trends - Hemsel, Tobias; Littmann, Walter; Wallaschek, Jörg (Ultrasonics Symposium, 2002. Proceedings. 2002 IEEE)
Piezoelectric transformers are well known since the publication of some patent applications at the end of the 1950s. But until today their only business use lies in the field of backlighting systems for LCDs. Due to key features as light-weight, flatness, high step-up at low volume and high efficiency piezoelectric transformers should be usable in a much broader range of applications. This contribution returns to mind their operating principle, shows how to model and to develop such devices as well as give some aspects for development trends that will lead to further applications.
Keywords: piezoelectric devices; reviews; transformers; backlighting systems; flatness; high efficiency piezoelectric transformers; high step-up; light-weight; low volume; operating principle; piezoelectric transformers; Circuits; Costs; Electromagnetic devices; Electromagnetic fields; Mechanical energy; Piezoelectric materials; Power electronics; Switching frequency; Transformers; Vibrations

Piezoelektrische Transformatoren - Bauformen und Modellierung - Hemsel, Tobias; Littmann, Walter; Wallaschek, Jörg (47. Internationales Wissenschaftliches Kolloquium)

Optimization of the Contact Geometry between Turbine Blades and Underplatform Dampers with respect to Friction Damping - Panning, Lars; Sextro, Walter; Popp, Karl (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)

Spatial dynamics of tuned and mistuned bladed disks with cylindrical and wedge-shaped friction dampers - Panning, Lars; Sextro, Walter; Popp, Karl (Proceedings of the 9th International Symposium on Transport Phenomena and Dynamics of Rotating Machinery, ISROMAC)

Fast Calculation of the Statistics of the Forced Response of Mistuned Bladed Disk Assemblies with Friction Contacts - Sextro, Walter; Panning, Lars; Götting, Florian (Proceedings of ASME TURBO Expo, Power for Land, Sea, and Air)

Optimierung des Schwingungsverhaltens elastischer Strukturen mit Reibfugen - Sextro, Walter; Popp, Karl (Forschungsvereinigung Verbrennungskraftmaschinen (FW) - lnformationstagung Turbinen)

Untersuchung und Weiterentwicklung linearer piezoelektrischer Schwingungsantriebe - Hemsel, Tobias

Schwingungsanalyse verstimmter Schaufelkränze mit Reibelementen - Panning, Lars; Sextro, Walter; Popp, Karl (Schwingungen in rotierenden Maschinen VI SIRM, Referate der Tagung in Wien)

Heat and Wear Generation for Rolling Contacts - Sextro, Walter (Zeitschrift für angewandte Mathematik und Mechanik (ZAMM))

Development and Experimental Validation of a Point Contact Model for Dynamical Problems with Friction - Sextro, Walter (ASME Design Engineering Technical Conferences)

Localization in Nonlinear Mistuned Systems with Cyclic Symmetry - Sextro, Walter; Popp, Karl; Krzyzynski, Tomasz (Nonlinear Dynamics)
In forced systems with cyclic symmetry localization can occur due toparameter uncertainties. Often, Monte-Carlo simulations are used to findregions, where the system response is sensitive to parameteruncertainties. These simulations require a large computation time.Therefore, an approximate method to calculate the envelopes of thefrequency response functions is developed in this paper. An example of anonlinear system with cyclic symmetry is a bladed disk assembly withfriction dampers. Friction dampers can be installed underneath the bladeplatforms of turbine blades. Due to dry friction and the relative motionbetween blades and dampers, energy is dissipated, which results in areduction of blade vibration amplitudes. By optimizing the mass of thefriction dampers, the best damping effects are obtained, which lead toan increase in the reliability of the turbine. In this paper, thecalculated response of a mistuned bladed disk assembly with frictiondampers is discussed. An approximate method is developed to calculatethe envelopes of the corresponding frequency response function forstatistically varying eigenfrequencies of the blades. Regions wherelocalization can occur with a high probability, are calculated by thismethod.
Keywords: bladed disk assembly; mistuning; sensitivity; localization

Piezoelektrische lineare Schwingungsantriebe - Wallaschek, Jörg; Hemsel, Tobias (Special Antriebstechnik)

Survey of the present state of the art of piezoelectric linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics)
Piezoelectric ultrasonic motors have been investigated for several years and have already found their first practical applications. Their key feature is that they are able to produce a high thrust force related to their volume. Beside rotary drives like the travelling wave motor, linear drives have also been developed, but only a few are presently commercially available. In the present paper, we first describe the state of the art of linear piezoelectric motors. The motors are characterized with respect to their no-load velocity, maximum thrust force, efficiency and other technical properties. In the second part, we present a new motor, which is judged to be capable of surpassing the characteristics of other piezoelectric motors because of its unique design which allows the piezoelectric drive elements to be pre-stressed in the direction of their polarization. The piezoelectric elements convert energy using the longitudinal d33 effect which allows an improved reliability, large vibration amplitudes and excellent piezoelectric coupling. Energy loss by vibration damping is minimized, and the efficiency can be improved significantly. Experimental results show that the motor characteristics can be optimized for a particular task by choosing the appropriate operating parameters such as exciting voltage, exciting frequency and normal force.
Keywords: Linear motor

State of the art and development trends of ultrasonic linear motors - Hemsel, Tobias; Wallaschek, Jörg (Ultrasonics Symposium, 2000 IEEE)
Ultrasonic linear motors have now been investigated for several years. Their key features are high thrust forces related to their volume and good position-accuracy. This contribution consists of two main parts. In the first part we describe the state-of-the-art of linear piezoelectric motors. Characteristics like no-load velocity, maximum thrust force and other technical properties of commercially available devices will be reported as well as those of prototypes. In the second part we report an ongoing research and development project aiming at a linear piezoelectric motor, which is capable of surpassing some of the shortcomings of other piezoelectric motors
Keywords: linear motors; ultrasonic motors; linear piezoelectric motor; maximum thrust force; no-load velocity; ultrasonic linear motor; Electromagnetic devices; Electromagnetic fields; Frequency; Friction; Gears; Materials science and technology; Piezoelectric materials; Research and development; Vibrations; Wheels

Piezoelectic linear motors - Hemsel, Tobias; Wallaschek, Jörg (Tagungsband der ACTUATOR)

Stand der Technik und Entwicklungsperspektiven linearer piezoelektrischer Schwingungsantriebe - Hemsel, Tobias; Wallaschek, Jörg
Piezoelektrische Schwingungsantriebe sind Kleinmotoren, deren Funktionsprinzip darin besteht, dass elektrische Energie mit Hilfe von Piezokeramiken in mechanische Schwingungsenergie gewandelt und diese dann durch hochfrequente Kontaktvorgänge auf den anzutreibenden Teil übertragen wird. Der Stand der Technik auf dem Gebiet piezoelektrischer Linearantriebe zeigt, dass viele piezoelektrische Linearantriebe bereits zufriedenstellende Leistungsmerkmale aufweisen. Gleichzeitig ist zu erwarten, dass die Leistungen dieser Antriebe noch deutlich verbessert werden können. Ein Ansatz, insbesondere den Wirkungsgrad und die mechanische Leistung zu erhöhen, wird anhand eines Motors aufgezeigt, der am Heinz Nixdorf Institut entwickelt wurde. Eine Übersicht der in ausgewählten Einsatzgebieten geforderten Leistungsdaten führt auf Entwicklungsziele für bestehende und neuartige piezoelektrische Linearantriebe.